(untitled) (The Review of Diabetic Studies, 2025)
To assess Quality of Life Improvement following Emicizumab prophylaxis in severe Haemophilia- A patients To evaluate the impact on ABR and functional independence in hemophilia A patients. To assess the quality-of-life improvement in severe hemophilia patients on Emicizumab prophylaxis for the period of 6 months